Survey of the current status of subclinical coronavirus disease 2019 (COVID-19). Issue 12 (December 2020) - Matsuba, Ikuro; Hatori, Nobuo; Koido, Norihiko; Watanabe, Yoshiyuki; Ebara, Futoshi; Matsuzawa, Yoko; Nishikawa, Tetsuo; Kunishima, Tomoyuki; Degawa, Hisakazu; Nishikawa, Masanori; Ono, Yoshiaki; Kanamori, Akira
Abstract: Objectives: We investigated relationships between subclinical COVID-19 (coronavirus disease 2019) and background factors. Methods: We determined SARS-CoV-2 antibody (IgG) prevalence in 1603 patients, doctors, and nurses in 65 medical institutions in Kanagawa Prefecture, Japan and investigated their background factors. Antibodies (IgG) against SARS-CoV-2 were analyzed by Immunochromatographic test. Results: The 39 subjects (2.4%) were found to be IgG antibody-positive: 29 in the patient group (2.9%), 10 in the doctor/nurse group (2.0%), and 0 in the control group. After adjustment for age, sex, and the antibody prevalence in the control group, antibody prevalence was 2.7% in the patient group and 2.1% in the doctor/nurse group. There was no significant difference between the antibody-positive subjects and the antibody-negative subjects in any background factors investigated including overseas travel, contact with overseas travelers, presence/absence of infected individuals in the living area, use of trains 5 times a week or more, BCG vaccination, and use of ACE inhibitor and ARB. Conclusions: Antibody prevalence in the present survey at medical institution is higher than that in Tokyo and in Osaka measured by the government suggesting that subclinical infections are occurring more frequently than expected. No background factor that influenced antibody-positive status due to subclinical infection was identified.